VOLATILE ELEMENT ABUNDANCE PATTERNS AND AN EARLY LIQUID WATER OCEAN ON EARTH - Kramers J.D. (My University, 2003)
The abundances of the elements H, C, N, Ne, primordial Ar, Cl, Br, Kr, I and Xe, in the atmo-hydrosphere, continental crust and MORB-source mantle (termed the outer Earth reservoirs (OER)) are examined and compared with solar matter and an average of carbonaceous chondrites (CC). The aim is to assess the likelihood of various possible sources for these volatile elements now on Earth, and discuss and possibly quantify processes whereby volatiles were lost, in order to narrow down scenarios for the earliest terrestrial environment.
Keywords: Terrestrial volatiles; Atmosphere loss; Hadean ocean; Hydrodynamic escape